Sequence domains required for the activity of avirulence genes avrB and avrC from Pseudomonas syringae pv. glycinea. - Tamaki, S J (1991)
avrB and avrC from Pseudomonas syringae pv. glycinea share significant amino acid homology but interact with different soybean resistance genes to elicit the hypersensitive defense reaction. Recombinant genes constructed between avrB and avrC revealed that the central regions were required for avirulence gene activity but the 5' and 3' termini were interchangeable. Recombinants involving the central regions did not yield any detectable avirulence gene activity, and no new avirulence phenotypes were observed from any of the chimeric genes. These results suggest that the protein products of avrB and avrC possess catalytic properties that are required for the avirulence phenotypes.